2006
DOI: 10.1039/b609029j
|View full text |Cite
|
Sign up to set email alerts
|

Dual colour, microarray-based, analysis of 10 000 protease substrates

Abstract: A 10,000 member PNA-encoded library of FRET based peptides was synthesised for global analysis of protease cleavage specificity; analysis was achieved using a DNA microarray and consumed minimal quantities of enzyme (60 pmole) and library (3.5 nmole).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…6 Detection of proteolytic cleavage on peptide arrays reading surface-bound fragment. a Internally fluorescence-quenched peptides on arrays, subsequent to cleavage peptide fragment containing quenching moiety is washed away yielding fluorescence increase for cleaved peptides [66,166,171]. b Peptides having a fluorogenic group C-terminal to the scissile bond which increases fluorescence subsequent to cleavage [175,181].…”
Section: Assays and Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Detection of proteolytic cleavage on peptide arrays reading surface-bound fragment. a Internally fluorescence-quenched peptides on arrays, subsequent to cleavage peptide fragment containing quenching moiety is washed away yielding fluorescence increase for cleaved peptides [66,166,171]. b Peptides having a fluorogenic group C-terminal to the scissile bond which increases fluorescence subsequent to cleavage [175,181].…”
Section: Assays and Detectionmentioning
confidence: 99%
“…Additionally, for protein-tyrosine kinase p60 c-src only incorporation of the long and hydrophilic 1-amino-4,7,10-trioxa-13-tridecanamine succinimic acid building block spacer allowed effective phosphorylation of the glass surface-bound peptides [26]. A similar linker structure was used to space apart Peptide Nucleic Acid (PNA) tags from potential protease substrates [66], protein serine/threonine kinase substrates [29,30] or tyrosine kinase substrates [67]. Inamori et al reported that insertion of a PEG spacer between chemoselective attachment point and the kinase substrate sequence improved phosphorylation efficiency by c-Src but not by PKA [35].…”
Section: Chemistry Of Peptide Array Preparationmentioning
confidence: 99%
“…Other types of soluble peptide libraries were prepared by individual coupling of peptides with DNA [232,233] or peptide nucleic acid [234] tags. After biotransformation of the peptide library in the solution assay (cleavage by protease, phosphorylation by kinase), the modified substrate was captured on a complementary DNA array and the structure of the substrate peptide was defined.…”
Section: Synthesis Of Peptide Mixturesmentioning
confidence: 99%
“…Such an approach has been applied to protease-activity analysis by utilizing peptide nucleic acid (PNA) encoding, [12][13][14] for phosphatase-activity screening with activity-based probes by expression display, [15] and we have used a similar approach to develop a protease-activity assay (I. A. Kozlov, et al, unpublished results).…”
Section: Introductionmentioning
confidence: 99%